Sosialisasi Pengembangan Potensi Wisata Di Kelurahan Padang Serai Melalui Pelatihan Dan Pendampingan Bagi Masyarakat Lokal - Susanto, Prio; Oktridarti, Levy; Tika, Yori Manis; Astuti, Linda; Sumarni, Hania; Shinta, Seftya Dwi; Indriani, Heni; Rosyadi, Imron (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
The development of tourism potential in Padang Serai Village has great potential to increase local community income and preserve the environment and culture. However, the development of tourism potential in Padang Serai Village is still not optimal. Therefore, it is necessary to conduct socialization of the development of tourism potential in Padang Serai Village through training and mentoring for the local community. The purpose of this service is to increase the awareness and ability of the local community in managing and developing tourism potential in Padang Serai Village. The method used in this service is training and mentoring for the local community. The results of this service show that the awareness and ability of the local community in managing and developing tourism potential in Padang Serai Village increased after training and mentoring. Therefore, this service can provide benefits to the local community and increase tourism potential in Padang Serai Village.